Biodegradable stents for the treatment of bowel strictures in Crohn's disease: technical results and challenges - Karstensen, John Gásdal; Christensen, Katrine Risager; Brynskov, Jørn; Rønholt, Claus; Vilmann, Peter; Hendel, Jakob (Endoscopy International Open, 2016)
Background and study aims: In patients with Crohn’s disease, the idea of biodegradable stents for treatment of bowel strictures with limited effect of endoscopic balloon dilation is tempting and initial results have been promising. The aim of this study was to evaluate the technical and clinical success of biodegradable stents for treatment of inflamed Crohn’s strictures refractory to endoscopic balloon dilatation.Patients and methods: Consecutive patients treated with biodegradable stents due to Crohn’s disease and inflamed bowel strictures refractory to endoscopic balloon dilatation were included. Technical and clinical success were evaluated.Results: Six patients were included in the study. Technical success was obtained in five patients (83 %). Clinical success was limited to one patient (20 %); failure was observed due to mucosal overgrowth (n = 2), stent migration (n = 1), and stent collapse (n = 1).Conclusions: In Crohn’s disease, it is technically feasible to treat bowel strictures with biodegradable stents. However, we have stopped using biodegradable stents due to lack of clinical success and side effects such as mucosal overgrowth and stent collapse.